2003
DOI: 10.3171/jns.2003.99.2.0402
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropic pituitary carcinoma: HER-2/neu expression and gene amplification

Abstract: The authors report on two gonadotropic carcinomas of the adenohypophysis that occurred in a55-year-old man (Case 1) and a 53-year-old woman (Case 2), with signs of mass effect and amenorrhea, respectively. Both lesions were macroadenomas. The tumor in Case 1 metastasized to dura mater, skull, nasal sinus, and larynx 2 years after patient presentation, whereas that in Case 2 spread to vertebral bodies and ribs after a 19-year latency. Histologically, the primary, recurrent, and metastatic lesions in Case 1 feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…Despite the benign histology of many of these tumors, life expectancy is usually less than one year from time of diagnosis. Furthermore, several reports have indicated that carcinomas likely arise from progressive malignant transformation of adenomas and associated ultrastructural or genetic alterations [12,13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benign histology of many of these tumors, life expectancy is usually less than one year from time of diagnosis. Furthermore, several reports have indicated that carcinomas likely arise from progressive malignant transformation of adenomas and associated ultrastructural or genetic alterations [12,13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Common distant metastatic sites are liver, cervical lymph nodes, bone and lung. [1][2][3][4][5][6]9,10,17 Only 39 cases of ACTHproducing pituitary carcinomas have been described in the literature to date. 8,10 Thirty-four of them were recently reviewed by Holthause et al, 18 and those authors noted that 16 (45%) cases exhibited extracranial …”
Section: Discussionmentioning
confidence: 99%
“…For instance, a myriad of genetic mutations has been re p o rted in such tumors 1 2 , 1 9 -2 1 , but their assessment has shown little, if any, clinical usefulness 1 2 . Besides, several biochemical and histopathological markers have recently been investigated in order to evalu- ate the etiopathology of pituitary carcinomas, but still without conclusive results [22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%